Reduced tactile sensitivity is associated with mild cognitive impairment - Löffler, Annette; Beier, Florian; Bekrater-Bodmann, Robin; Hausner, Lucrezia; Desch, Simon; Silvoni, Stefano; Kleinböhl, Dieter; Löffler, Martin; Nees, Frauke; Frölich, Lutz; Flor, Herta (EBioMedicine, 2024)
Background - Sensory impairment has been related to age-associated cognitive decline. While these associations were investigated primarily in the auditory and visual domain, other senses such as touch have rarely been studied. Thus, it remains open whether these results are specific for particular sensory domains, or rather point to a fundamental role of sensory deficits in cognitive decline. - Methods - Data from 31 participants with mild cognitive impairment (MCI), 46 participants with frailty, and 23 non-clinical control participants (NCCs) were included. We assessed sensory function using visual acuity and contrast sensitivity, hearing threshold, and mechanical detection threshold. Cognitive function in participants with MCI was assessed using associative memory performance. Group differences on sensory thresholds were tested using analyses of covariance with age, sex, and years of education as covariates. Associations between measures within participants with MCI were evaluated using Spearman correlations. - Findings - We found a significant difference in mechanical detection threshold between the groups (p < 0.001, η2 = 0.18). Participants with MCI showed significantly reduced tactile sensitivity compared to participants with frailty and NCCs. In participants with MCI, lower associative memory performance was significantly related to reduced tactile sensitivity (rs = 0.39, p = 0.031) and auditory acuity (rs = 0.41, p = 0.022). - Interpretation - Our results indicate that reduced tactile sensitivity is related to cognitive decline. Prospective studies should investigate the age-related alterations of multimodal sensory processes and their contribution to dementia-related processes. - Funding - Deutsche Forschungsgemeinschaft (FL 156/41-1) and a grant of the Hector-Stiftung II, Weinheim, Germany.